2013
DOI: 10.1111/all.12259
|View full text |Cite
|
Sign up to set email alerts
|

Components in soy allergy diagnostics: Gly m 2S albumin has the best diagnostic value in adults

Abstract: Specific immunoglobulin E to Gly m 2S albumin had the best accuracy in diagnosing soy allergy. Gly m 5 and 6 were related to mild symptoms. Higher levels of Gly m 4 were related to allergy to soy milk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
4
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 15 publications
(67 reference statements)
2
46
4
1
Order By: Relevance
“…7 Klemans et al also reported that Gly m 8 had the best accuracy in diagnosing soy allergy, although the AUC for this component was comparable to SPT and sIgE to soy extract. 8 Limitations of these previous studies examining soy components include their geographic limitations to Europe and Asia, their utilization of patients diagnosed with soy allergy without confirmation by OFC, and their comparison of IgE levels from subjects with soy allergy to negative controls who were known to tolerate soy and have significantly lower soy sIgE levels. 5-8 Here we analyze IgE results to the components Gly m 4, 5, and 6, as well as the new 2S albumin component, Gly m 8, among children from the US who underwent OFCs for the evaluation of suspected soy allergy.…”
Section: To the Editormentioning
confidence: 99%
“…7 Klemans et al also reported that Gly m 8 had the best accuracy in diagnosing soy allergy, although the AUC for this component was comparable to SPT and sIgE to soy extract. 8 Limitations of these previous studies examining soy components include their geographic limitations to Europe and Asia, their utilization of patients diagnosed with soy allergy without confirmation by OFC, and their comparison of IgE levels from subjects with soy allergy to negative controls who were known to tolerate soy and have significantly lower soy sIgE levels. 5-8 Here we analyze IgE results to the components Gly m 4, 5, and 6, as well as the new 2S albumin component, Gly m 8, among children from the US who underwent OFCs for the evaluation of suspected soy allergy.…”
Section: To the Editormentioning
confidence: 99%
“…In a group of 39 peanut-sensitized patients, 82, 55, and 87 % of patients were also sensitized to lupine, pea, and soybean, respectively, whereas, based on DBPCFC, 29–35 % had symptoms to these beans [20]. In a recent study, Klemens and colleagues showed that 60 % of soy-allergic patients had a concomitant peanut allergy and significantly more often specific IgE to soy extract, the soy 2S albumin Gly m 8 and the soy cupins Gly m 5 and Gly m 6 compared to the peanut-tolerant group [21•].…”
Section: Introductionmentioning
confidence: 99%
“…In a group of 39 peanut-sensitised patients, 82,55, and 87% of patients were also sensitised to lupine, pea, and soybean, respectively, whereas, based on DBPCFC, 29-35% had symptoms to these beans (Barre et al , 2008). In a recent study, Klemans et al (2013) showed that 60% of soy-allergic patients had a concomitant peanut allergy. The peanut allergic group often showed specific IgE to soy extract, soy 2S and Gly m 8 albumins and soy Gly m 5 and Gly m 6 cupins.…”
Section: Resultsmentioning
confidence: 99%